The Impact of Personalized Human Support on Engagement With Behavioral Intervention Technologies for Employee Mental Health: An Exploratory Retrospective Study - Jesuthasan, Jehanita; Low, Megan; Ong, Tiffanie (Frontiers in Digital Health, 2022)
Digital healthcare has grown in popularity in recent years as a scalable solution to address increasing rates of mental illness among employees, but its clinical potential is limited by low engagement and adherence, particularly in open access interventions. Personalized guidance, involving structuring an intervention and tailoring it to the user to increase accountability and social support, is one way to increase engagement with digital health programs. This exploratory retrospective study therefore sought to examine the impact of guidance in the form of personalized prompts from a lay-person (i.e., non-health professional) on users’ (N = 88) engagement with a 16-week Behavioural Intervention Technology targeting employee mental health and delivered through a mobile application. Chi-squared tests and Mann-Whitney tests were used to examine differences in retention and engagement between individuals who received personalized prompts throughout their 4-month program and individuals for whom personalized prompts were introduced in the seventh week of their program. There were no significant differences between the groups in the number of weeks they remained active in the app (personalized messages group Mdn = 3.5, IQR = 3; control group Mdn = 2.5, IQR = 4.5; p = 0.472). In the first 3 weeks of the intervention program, the proportion of individuals who explored the educational modules feature and the messaging with health coaches feature was also not significantly associated with group (ps = 1.000). The number of modules completed and number of messages sent to health coaches in the first 3 weeks did not differ significantly between the two groups (ps ≥ 0.311). These results suggest that guidance from a non-health professional is limited in its ability to increase engagement with an open access Behavioural Intervention Technology for employees. Moreover, the findings suggest that the formation of a relationship between the individual and the agent providing the guidance may be necessary in order for personalized guidance to increase engagement.